1980
DOI: 10.1083/jcb.87.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA processing and nuclear structure: isolation of nuclear ribonucleoprotein particles containing beta-globin messenger RNA precursors.

Abstract: To explore the relationships between transcription, messenger RNA (mRNA) processing, and nuclear structure, ribonucleoprotein particles containing heterogeneous nuclear RNA (hnRNP) have been purified from globin-producing mouse Friend erythroleukemia cells. These nuclear hnRNP particles sediment at 50S-2005 and contain, in addition to high molecular weight hnRNA, a specific set of nuclear proteins predominated by a major component of 38,000 mol wt . The hnRNP particles are free of histones and ribosomal struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
0
1

Year Published

1983
1983
2002
2002

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 47 publications
1
39
0
1
Order By: Relevance
“…One obvious possibility is hyperphosphorylation, which might reduce electrostatic interactions of hnRNP proteins with hnRNA. The effect could also be due to a sudden cessation of hnRNP protein translation upon heat shock, so that the preexisting nuclear pool of free hnRNP proteins (which appears to be small in the first place [41]) becomes rapidly depleted after heat shock. We do not think that the effect on hnRNP assembly is actually dependent on the heat shock proteins themselves, because it can be observed within 10 min after heat shock (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One obvious possibility is hyperphosphorylation, which might reduce electrostatic interactions of hnRNP proteins with hnRNA. The effect could also be due to a sudden cessation of hnRNP protein translation upon heat shock, so that the preexisting nuclear pool of free hnRNP proteins (which appears to be small in the first place [41]) becomes rapidly depleted after heat shock. We do not think that the effect on hnRNP assembly is actually dependent on the heat shock proteins themselves, because it can be observed within 10 min after heat shock (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These heterogeneous nuclear RNP (hnRNP) particles contain protein and RNA in a mass ratio of about 4:1 (7,38,42). A remarkable property of hnRNP particles is their ability to withstand isopycnic banding in Cs2SO4 without prior aldehyde fixation (7,41). We have isolated hnRNP particles from Drosophila KcO cells (S. Mayrand and T. Pederson, unpublished data) and have found that they also are stable during centrifugation in Cs2SO4 and band at 1.34 g/cm3, which indicates the same 4:1 protein-RNA composition as mammalian hnRNP (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first described spliceosome proteins were called hnRNP proteins, based on their association with large heterogeneous nuclear RNA transcripts now known to include unspliced pre-mRNAs (6)(7)(8)(9)(10)(11)(12). The C-group hnRNP proteins are abundant nuclear proteins of Mr 42,000-44,000 that have been implicated in splicing (13,14) and are known to be phosphorylated in vivo (8,(15)(16)(17) by a casein kinase II-type activity (18,19).…”
mentioning
confidence: 99%